Histopathologic changes in guinea pig mastoid mucosa after topical mitomycin C application followed by mastoidectomy - Ozturk, Levent; Kaygusuz, Irfan; Akpolat, Nusret; Keles, Erol; Karlidag, Turgut; Alpay, Hayrettin Cengiz; Yalcin, Sinasi (W B Saunders Co-Elsevier Inc, 2008)
Purpose: This study was performed to investigate the histopathologic changes observed in mastoid cavity of guinea pigs after the application of mitomycin C after mastoidectomy. Materials and methods: The study was performed oil 50 guinea pigs. Unilateral (right ear) mastoidectomy was performed on all guinea pigs. Twenty-five guinea pigs were separated as Study group and the remaining were separated as control group. A mitomycin C-soaked sponge was placed in the mastoid cavities of the study group and a dry sponge was placed in those of the control group. Their mastoid cavities were examined histopathologically for absorbable sponge waste, abscess formation, fibrosis, vascularization, polymorphonuclear leukocyte infiltration, edema, lymphoplasmacytic inflammatory infiltration, and granulation tissue. Results: Absorbable sponge waste, abscess formation. fibrosis, vascularization, edema, and lymphoplasmacytic inflammatory infiltration were not significantly different between the groups, However, polymorphonuclear leukocyte infiltration and granulation tissue were statistically different between the groups. Conclusion: Mitomycin C can be used after mastoidectomy to decrease the granulation tissue formation in car discharges and to prevent the discharge. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Chronic Otitis-Media; Pterygium Surgery; Choanal Atresia; Repair